Influence of the Reactive Strength Index Modified on force- and power-time curves - McMahon, J. J.; Jones, P. A.; Suchomel, T. J.; Lake, J.; Comfort, P. (International Journal of Sports Physiology and Performance, 2018)
Purpose: The Reactive Strength Index Modified (RSImod) has been recently identified and validated as a method of monitoring countermovement-jump (CMJ) performance. The kinetic and kinematic mechanisms that optimize a higher RSImod score are, however, currently unknown. The purpose of this study, therefore, was to compare entire CMJ force-, power-, velocity-, and displacement-time curves (termed temporal-phase analysis) of athletes who achieve high versus low RSImod scores. Methods: Fifty-three professional male rugby league players performed 3 maximal-effort CMJs on a force platform, and variables of interest were calculated via forward dynamics. The top (high RSImod group) and bottom (low RSImod group) of 20 athletes` CMJ kinetic- and kinematic-time curves were compared. Results: The high-RSImod group (0.53±0.05 vs 0.36±0.03) jumped higher (37.7±3.9 vs 31.8±3.2 cm) with a shorter time to takeoff (TTT) (0.707±0.043 vs 0.881±0.122 s). This was achieved by a more rapid unweighting phase followed by greater eccentric and concentric force, velocity, and power for large portions (including peak values) of the jump, but a similar countermovement displacement. The attainment of a high RSImod score therefore required a taller, but thinner, active impulse. Conclusions: Athletes who perform the CMJ with a high RSImod, as achieved by high jumps with a short TTT, demonstrate superior force, power, velocity, and impulse during both the eccentric and concentric phases of the jump. Practitioners who include the RSImod calculation in their testing batteries may assume that greater RSImod values are attributed to an increase in these underpinning kinetic and kinematic parameters.